ALLAPININE EFFECTIVENESS IN PATIENTS WITH CORONARY HEART DISEASE AND CARDIAC ARRHYTHMIAS - A. G. Mrochek; E. N. Gubar’ (Российский кардиологический журнал)
The paper reviews the currently available evidence on cardiac arrhythmia treatment, in particular, on allapinine therapy. The original data on allapinine effectiveness, obtained in 24 patients with different variants of cardiac arrhythmias, are presented.